Mediterranean woody agroecosystems in a warming and drier climate: the importance of knowledge-based management - Pinheiro, Carla (2022)
The Mediterranean region is often described as a climate change hotspot. Not surprisingly, climate change impact on Medieterranean Agroecosystems sustainability, biodiversity, and productivity has been receiving a lot of interest from the research community. It is reported that the frequency, intensity and duration of droughts, as well as hotter droughts, are interfering with ecosystems’ structure, composition, and functions. To minimize some of the risks of the ongoing climate change, and maintain the economic viability of the agroecosystems, management strategies and practices need to be changed/adapted at the local and regional levels. This is of fundamental importance for the design of future human societies and their relationships with other species